2020
DOI: 10.1080/20018525.2020.1861580
|View full text |Cite
|
Sign up to set email alerts
|

An RCT of acute health effects in COPD-patients after passive vape exposure from e-cigarettes

Abstract: Background: E-cigarette use has been shown to have short-term acute effects among active users but less is known of the acute passive effects, particularly among individuals with existing respiratory diseases. Objective: To investigate local and systemic effects of short-term passive vape exposure among patients with mild or moderate chronic obstructive pulmonary disease (COPD). Methods: In a double-blinded crossover study 16 non-smoking COPD-patients (mean age 68) were randomly exposed for 4 h to passive vape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A randomized controlled trial examined the effects of passive ENDS aerosol exposure in patients who had COPD who were nonsmokers. 218 Passive e-cigarette exposure resulted in alterations in exhaled surfactant protein A and increases in certain plasma proteins that could indicate inflammation. 218 In a large cross-sectional telephone survey of never-smokers, the odds of self-reported asthma were higher in current ENDS users compared with nonusers.…”
Section: Chronic Health Effects Of E-cigarettes and Vaping Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled trial examined the effects of passive ENDS aerosol exposure in patients who had COPD who were nonsmokers. 218 Passive e-cigarette exposure resulted in alterations in exhaled surfactant protein A and increases in certain plasma proteins that could indicate inflammation. 218 In a large cross-sectional telephone survey of never-smokers, the odds of self-reported asthma were higher in current ENDS users compared with nonusers.…”
Section: Chronic Health Effects Of E-cigarettes and Vaping Productsmentioning
confidence: 99%
“…218 Passive e-cigarette exposure resulted in alterations in exhaled surfactant protein A and increases in certain plasma proteins that could indicate inflammation. 218 In a large cross-sectional telephone survey of never-smokers, the odds of self-reported asthma were higher in current ENDS users compared with nonusers. 219 Similar survey studies have shown higher self-reported asthma and COPD in ENDS users.…”
Section: Chronic Health Effects Of E-cigarettes and Vaping Productsmentioning
confidence: 99%
“…Levels of SP-A and albumin are typically assessed by bronchoalveolar lavage (BAL) or similar invasive methods, but new technology makes it possible to measure these proteins in droplets in exhaled air [ 32 , 33 ]. To date, the measurement of SP-A and albumin in exhaled air has not been studied in relation to exposure to air pollution, but effects on SP-A have been found in an exposure study of second-hand emissions from electronic cigarettes and in a cross-sectional study of smokers [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, concerns about e-cigarette harms include negative impact on cardiovascular health [ 7 ] and potential hazards such as obstructive lung disease from flavorants in e-cigarettes [ 8 ]. Passive exposure to second hand aerosol (SHA) from e-cigarettes is also a cause for concern, especially among those with respiratory diseases such as COPD [ 9 , 10 ], and symptoms of sensory irritation, and general complaints have been reported by non-smokers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%